2017
DOI: 10.1128/aac.01582-16
|View full text |Cite
|
Sign up to set email alerts
|

Low Caspofungin Exposure in Patients in Intensive Care Units

Abstract: In critically ill patients, drug exposure may be influenced by altered drug distribution and clearance. Earlier studies showed that the variability in caspofungin exposure was high in intensive care unit (ICU) patients. The primary objective of this study was to determine if the standard dose of caspofungin resulted in adequate exposure in critically ill patients. A multicenter prospective study in ICU patients with (suspected) invasive candidiasis was conducted in the Netherlands from November 2013 to October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 54 publications
(76 reference statements)
2
43
0
Order By: Relevance
“…As shown in the current study, hyperbilirubinemia and hypoalbuminemia may represent two such counteracting factors. There was a relatively large interindividual variation in the AUC 0 -24 and the other PK parameters, which is in agreement with previous studies on caspofungin pharmacokinetics in ICU patients (14,15,18). The AUC 0-24 values in our patients compared with those observed in these studies and healthy subjects are shown in Table S4 in the supplemental material.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in the current study, hyperbilirubinemia and hypoalbuminemia may represent two such counteracting factors. There was a relatively large interindividual variation in the AUC 0 -24 and the other PK parameters, which is in agreement with previous studies on caspofungin pharmacokinetics in ICU patients (14,15,18). The AUC 0-24 values in our patients compared with those observed in these studies and healthy subjects are shown in Table S4 in the supplemental material.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the case of fluconazole there has been good agreement between human and murine data (24,25). As previously proposed for anidulafungin (17) and caspofungin (18), current data suggest that therapeutic drug monitoring (TDM) is relevant in critically ill In addition to being considerably larger than previous studies, the strength of the present study is its separate analyses of individual components of the C-P score, demonstrating counteracting effects of bilirubin and albumin. Thus, by expanding the knowledge of liver function and how PK parameters are affected in the critically ill, we can make more robust decisions on dosage of caspofungin.…”
Section: Discussionsupporting
confidence: 75%
“…Recent studies showed that echinocandins exposure in ICU patients was low compared with healthy volunteers and other (non-)critically ill patients, most likely as a result of a larger volume of distribution, suggesting that a weight-based dose regimen should probably be more suitable for patients with substantially altered drug distribution [45][46][47].…”
Section: Invasive Candidiasismentioning
confidence: 99%
“…TDM is not recommended for the echinocandins or amphotericin B by the current guidelines, although studies report significant variability in echinocandin exposure in specific patient populations [56,[63][64][65]. Decreased and potentially inadequate echinocandin exposure induced by physiological changes in critically ill patients may result in ineffective treatment and drug resistance [63][64][65].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Decreased and potentially inadequate echinocandin exposure induced by physiological changes in critically ill patients may result in ineffective treatment and drug resistance [63][64][65]. Although in vitro studies have shown a concentration-effect relationship, a clear relationship between exposure and therapeutic response is currently lacking [60].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%